The influence of graduate’s employability skills towards management expectation - Syamim Musfirah, Mohd Shah (2020)
Employability skills is significant in obtaining job for students. This is because, employer have their own requirement when hiring employee. Thus, students must fulfill those criteria needed by the employer. The aim of this study is to determine the influence of graduate employability skills namely basic skills; thinking skills; resource skills; information skills; interpersonal skills; system and technology skills; and personal quality towards management expectation. The sample of the study consist of 150 companies listed in Federation of Malaysian Manufacturers (FMM). Data was collected using Google Form Survey. Result shows that basic skills ranked first as the most important skills organization perceived followed by interpersonal skills and personal quality. Multiple regression result indicated that personal quality had significance influence towards management’s expectation. Overall, this study may give impact to the higher institution, academicians, and students in fulfilling those criteria needed by employer